Poor Eating Habits are the Primary Factor in Obesity -Induced NCD Vulnerability in Young Gabonese Adults - Ongali, Brice; Akoume, Marie-Yvonne; Okolongo, Serge Christian Mayani; Moutsinga, Alain; Lemamy, Guy Joseph (British Journal of Healthcare and Medical Research, 2026)
We previously reported obesity as an important behavioural risk factor for chronic non-communicable diseases (NCDs), which are increasingly prevalent among young, active populations in Gabon (Ongali et al., 2020). However, which one among lifestyle and diet remains the most responsible for the development of obesity is still debated. Herein, we investigate the relative impact of sedentary lifestyles versus poor dietary habits on obesity development within a university setting. Our findings reveal obesity rates of 18% among male students and 27% among female students. The data highlight that while physical inactivity contributes to weight gain, poor dietary habits, characterized by high consumption of fast food and sugary beverages, alongside irregular meal patterns, are the predominant drivers. These results suggest that dietary choices are the primary factor increasing NCD vulnerability among young Gabonese adults. This study calls on public health authorities to carry out awareness campaigns and take steps to combat obesity among young people to prevent NCD.